Collection and initial evaluation of Gliricidia sepium from Costa Rica - Sumberg, J.E. (Springer, 1985)
Describes a recently completed collection of Gliricidia sepium germplasm in Costa Rica. Presents and describes some characteristics of the collection sites and the range of variation in some plant characteristics.